Less-known Flowering Plants in the Neighbourhood of Puducherry South-eastern India - Ponnuchamy, R.; Pragasam, A.; Aravajy, S.; Anupama, K. (Indian Forester, 2014)
A qualitative-floristic survey was conducted in the outskirts of Puducherry, south-eastern India, in the year 2011. A total of 431 species from 78 families were determined during the survey. Thirteen of these species, belonging to 12 genera and 11 families were of less known occurrence in this region. The regional floras indicate that nine of these species are distributed from the coast to the plains and four in hilly areas. Among the species three are not common in the Tamilnadu Carnatic region. Two of the listed species, Cynanchum tunicatum (Retz.) Alston and Crotalaria evolvuloides are reported for the first time from the Puducherry region. These plants have become endangered severely due to anthropogenic pressures. The documented species require rapid conservation efforts to mitigate their loss.